Analisis Tingkat Partisipasi Masyarakat Terhadap Program Desa Vokasi Di Desa Pulutan Wetan Kecamatan Wuryantoro Kabupaten Wonogiri - Pratiwi, Monita Rossy, Drs. Dahroni, M.Si, Dra. Hj. Umrotun, M.Si (2015)
The research conducted in Pulutan Wetan Village, Wuryantoro Sub-district was aimed to: (1) Analysis of factor, process, and pattern that influence the degree of community participation in the program of vocational village in Pulutan Wetan Village, Wuryantoro Sub-district, Wonogiri Regency. (2) Analysis physical influence suitability and region competency against vocational village program. (3) Analysis the degree of community participation against vocational village program in Pulutan Wetan Village. (4) Analysis the influence of the program of vocational village againts the welfare of the community in Pulutan Wetan Village. There are 5 groups of vocational entrepreneur with 20 participants on research area. The research method using cencus method, because it is very effective to view in detail community participation analysis because the number of respondent only 100 people. Scoring method that used on every questionnaire. Classified with Sturges formula that is calculation which determine the amount of class on interval data grouping with the most data. The result showed that the factors which influence the degree of community participation against vocational village program are: education level, opinion level, type of employment, motivation of community and community perception; more higher the degree of education more lower the participation of community. Whereas the factors which do not affect community participation program of vocational village is: age, institutional,community, and character of the resource person. Geographical conditions and potential of the region is also able to affect the success of the program. One of them, soil type grumusol help greatly the development of vegetable cultivation. The results showed as much as 50% higher participation category on vegetable cultivation and 60% of the respondents had vocational village program in screen printing. Medium categories with 50% to the value of cultivating catfish, results inlow categories in traditional herbal busineses showed participation 40% and goat farming also low 65%. The impact of the program in the form of increased economic, social, and culture change; the internal supporting factors is the high achievement improving the quality of life and supporting external factor is the construction of the relevant institutional. Factor restricting the internal is the low motivation. Factors restricting the external was limited to capital